Alteracoes metabolicas decorrentes da delecao genica da enzima conversora de angiotensina 2 - ECA2 - em camundongos - Souza, Valéria Nunes de (2014)
Individual genetic susceptibility, inadequate nutrition and sedentary lifestyle figure among the most relevant risk factors for the emergence of cardiovascular and metabolic diseases. In this context, the two axes of the renin-angiotensin system (RAS), Angiotensin Converting Enzyme–Angiotensin II–AT1 receptor and Angiotensin Converting Enzyme 2–Angiotensin-(1-7)–Mas receptor, participate in central homeostatic regulatory mechanisms. Angiotensin Converting Enzyme 2 (ACE2) acts in an attempt to counteract the actions mediated, mainly, by Angiotensin II. In this scenario, the relevant action of ACE2 in the cardiovascular regulation has already been suggested, but the participation of such enzyme in glucose and lipid homeostasis still remains controversial. Thus, the aim of this work was to characterize the lipid and glucose metabolic alterations resulting from the gene deletion of ACE2 in C57BL/6 and apolipoprotein E knockout (ApoE-/-) mice, as well as the main mechanisms involved. C57Bl/6 and ACE2-/y mice were assessed at 3, 6 and 12 months of age after consumption of standard diet (Kcal, 10% lipids) and at 6 and 12 months of age after consumption of high fat diet (Kcal, 45% lipids). ApoE/ACE2-/y mice at 6 months of age were also used in the study. The gene deletion of ACE2 caused a paradoxical metabolic effect: at all ages assessed, ACE2 knockout animals presented a marked reduction in body weight, white adipose tissue deposition and systemic lipid profile. This event is associated with a lower susceptibility to high fat diet-induced obesity in animals at 6 months of age, but not at 12 months of age. Nevertheless, such gene deletion induced both steatosis and impairment in insulin signaling in the liver. The probable mechanism involves the increase of CD36 gene expression and the protein decrease of sirtuin 1 and protein kinase A in the liver, coupled with high expression of UCP2, a mitochondrial uncoupling protein which main function is control the production of oxidants. Furthermore, different from the results in the liver, systemically, ACE2-/y animals present greater glucose tolerance and greater insulin sensitivity. These results are due to lower fat deposition in these animals, coupled with increased expression of genes involved in insulin regulation in the white adipose tissue and in the muscle. Similar to the ACE2-/y animals, the double gene deletion (ApoE/ACE2-/y) attenuated the dyslipidemic metabolic profile of ApoE-/- animals, resulting in a systemic phenotype similar to that observed in ACE2-/y, for example: reduction in body weight, triglyceride levels and free fatty acids in plasma, along with the hepatic steatosis caused by mechanisms dependent on the increase in the CD36 pathway and reduction in the hepatic sirtuin 1 pathway. The new findings indicate that ACE2 and/or the “new axis” of the RAS have a central role in the regulation of glucose and lipid metabolism both systemically and in the liver, and probably, by an age-dependent mechanism. ACE2 deletion in mice involves the protection against high fat diet-induced obesity, but not steatosis. In this sense, ACE2-/y is a new animal model of lipodystrophy and represents a tool for investigating new metabolic treatments.